E-Learning in Practical Coures of Physical Education and Sports During Pandemic - Rif'iy Qomarrullah; Milcha H. Tammubua; Rivaldhy N. Muhammad; Suratni; Lestari Wulandari S; Tri Setyo Guntoro; Jonni Siahaan (Universitas Pendidikan Ganesha, 2023)
Physical education and sports can be a means of learning in encouraging students' physical and mental knowledge, appreciation, and reasoning. The main goal to be achieved in this research is to examine and describe the effectiveness of e-learning in physical education and sports education courses. This research is in the form of a quantitative survey with 33 samples using a total sampling technique. Data collection techniques using observation, questionnaires, field notes, and documentation. Data analysis used a quantitative descriptive method with a percentage scale. The results of this study indicate that there are two essential elements that lecture activities using online media have been implemented effectively. In the opinion of students as students, the implementation has been carried out according to the provisions. However, there are still some obstacles and obstacles, especially the internet network. Therefore, things still a barrier, such as signals and devices used during lectures, can be worked around with the group study method and determining an excellent point to get an internet network.